Multi - mechanism coalescence design and matrix expression of logic action sequences of the over-turn nursing robot Part II: Gesture-state in sets and matrix - Gu, Lizhi; Gao, Shanping; Gu, Chunyang; Huang, Yuantang; Xu, Feiyue; Zhong, Xiang; Chen, Kai; Song, Jinling (Institute of Physics Publishing, 2020)
As is expressed in Part I, Functions and coalescence design of the over-turn nursing robot, the performance and requirements have been put forward with systematic design of several mechanisms. Here, in order to control and function well the over-turn nursing robot, the three-dimensional and five-dimensional Euclidean space with the real number were adopted in terms of sets for gesture of the bedridden person and the corresponding state of the robot, respectively. The matrix method was employed to define and describe the gestures-robot performance and its transition path. The gesture-state sequence matrix not only accurately and clearly expressed the gesture series, state sequence and their corresponding relations, but also laid a theoretical and technical foundation for the path planning from the current gesture to the target one. The control and operation of 7 states and 5 gestures were done to realize the automation and intelligent over-turning safely, comfortably and conveniently.